Planktonic and Benthic Foraminifera Miocene on Sandstone Unit of Bentang Formation in Pangandaran, West Java (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The research in Pangandaran was due to the presence of exposed rock lithology and thepresence of fossil content, either macrofossil or microfossil. Research sites are located at108°27'46.55'' to 108°30'29.88''E and 7°41'35.54'' to 6°38'53.60''. This study was conducted todetermine the distribution of foraminifera contained in the constituent sandstone units of the BentangFormation. The research was conducted at 7 (seven) points of location of sandstone outcrops.Analysis and identification of foraminifera using a binocular microscope after foraminiferapreparation. The distribution areas of the sandstone units of the study area are in the Cimanggu, BulaKrandu and Karangbenda areas. Age datum markers that are characterized by planktonicforaminifera fossils, namely Sphaerodinellopsis multilobe and Globigerinoides ruber. Benthicforaminifera dominated by Lenticulina suborbicularis, Nouvigerina ampulaceae, Cibicidestenuimargo, Anomalinoides globulosus, Heterolepa praecincta, Ammonia convexa reflects a shallowmarine bathymetry zone or mid neritic (50-100m). Based on the content of planktonic and bentonicforaminifera, the sandstone units of the Bentang Formation were deposited during the MiddleMiocene (N12-N13) age in a shallow marine depositional environment
Keywords: Foraminifera; Sandstone Unit; Bentang Formation; Pangandaran